Treatment results evaluation using the Index of Orthodontic Treatment Need - Thalca Hamid (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: The use of orthodontic indices were increasingly popular in the last few years. Index of Orthodontic Treatment Need (IOTN) usually was used to assess the needs and demand of orthodontic treatment, eventhough, indices can be used for more than one purpose. Purpose: To determine whether the Index of Orthodontic Treatment Need (IOTN) could be able to evaluate the treatment results as well. Method: Data was obtained by evaluating each of 202 study models from 17 Orthodontic Postgraduate students. The ‘before’ and ‘after’ treatment models were assessed, using the Index of Orthodontic Treatment Need. Result: Using the Wilcoxon Signed-Rank test, the assessment of Dental Health Component (DHC) and Aesthetic Component (AC), before and after orthodontic treatment showed significantly differences from each others (p : 0,000 < α : 0.05). The Null hypothesis were rejected. The grade of DHC and AC were decreasing to a better score. Conclusion: The Index of Orthodontic Treatment Need (IOTN) could be used to assess the orthodontic treatment outcomes, to evaluate before and after orthodontic treatment of the patients. The results of the treatment showed good improvements of dentofacial appearance of the patients which means the successful achievement of the clinical works programs.